REKONSTRUKSI PERTANGGUNGJAWABAN PIDANA ATAS PENYEBARAN DEEPFAKE SEKSUAL TERHADAP PESERTA DIDIK DAN TENAGA PENDIDIK DI INDONESIA - Budoyo, Sapto; Khansa Pramesti, Fahrinda (Universitas Stikubank, 2026)
The development of generative artificial intelligence has given rise to a new form of digital-based sexual violence through the spread of sexual deepfakes, non-consensual synthetic sexual representations that can attack the dignity, privacy, sexual autonomy, and sense of security of victims. This threat becomes even more serious when targeting students and educators because it not only harms individuals but also disrupts the integrity and security of educational spaces. This study aims to analyze the construction of Indonesian criminal law in ensnaring the spread of sexual deepfakes in educational environments, identify weaknesses in its regulations, and formulate a more ideal reconstruction of criminal liability. The method used is normative legal research with a qualitative descriptive approach, through a literature review of laws and regulations, scientific literature, and relevant documents related to deepfakes, electronic-based sexual violence, and legal protection in educational environments. The results of the discussion indicate that Indonesian positive laws, such as the ITE Law, the TPKS Law, the Pornography Law, the Personal Data Protection Law, and educational regulations, have essentially provided a normative basis for prosecuting such acts, but they are still partial, fragmented, and do not explicitly regulate sexual deepfakes as a separate crime. Therefore, a reconstruction of criminal liability is needed that explicitly recognizes non-consensual synthetic sexual representation as a crime, expands the forms of punishable acts, provides for greater severity in the context of educational relations, and comprehensively integrates criminal penalties with victim protection and recovery. Keywords: sexual deepfakes, criminal liability, students, educators, digital-based sexual violence.